Needs for Innovation Leadership Development of Teachers under the Supervision of Samut Prakan Primary Educational Service Area Office 2 - Termvithi, Ungkana; เฉลิมวงศาเวช, วัลลภา (Al-HIKMAH Journal, 2022)
This research aimed to explore the current and desired states, needs for innovation leadership development. The subjects were 350 teachers under the supervision of Samut Prakan Primary Educational Service Area Office 2 in the academic year 2020. The instruments were a questionnaire and semi-structure interviews with three key informants. Data were analyzed using percentage, mean, standard deviation, and modified priority needs index (PNImodified). The result revealed that the current state and the desired state of innovation leadership of the teachers were at a moderate level (=3.49, S.D.=.68) and at a high level (=4.24, S.D.=.61), respectively. According to the result of need analysis, the highest ranges of PNImodified was displayed by support seeking (PNImodified=.249), followed by skill development (PNImodified=.234), innovation team management (PNImodified=.211), team building (PNImodified=.209), leadership performance (PNImodified=.201), and the creation of innovative climate (PNImodified=.190), respectively.